Interrelationships between obesity, blood pressure and metabolic profile in climacteric women - REIS,Vivianne Margareth Chaves Pereira (2021)
ABSTRACT Objective This study aimed to evaluate the interrelationships between obesity, blood pressure and metabolic profile in climacteric women. Methods This is a cross-sectional study with a random sample of 874 women, aged 40 to 65 years, assisted in Family Health Strategies units in Montes Claros, Minas Gerais, Brazil. A structural equation model was used to assess the interrelationships between obesity, blood pressure and metabolic profile, adjusted for age. The variables blood pressure, obesity and metabolic profile were treated as constructs, which measurement models were developed using confirmatory factor analysis. Results It was observed that age has a positive and significant effect on blood pressure (β=0.20; p<0.001) and obesity (β=0.10; p=0.004). There was a direct and positive effect of obesity on blood pressure (β=0.26; p<0.001) and on the metabolic profile (β=0.10; p=0.037), adjusted for physical activity. Conclusions The simultaneous analysis of the relationships between age, obesity, blood pressure and metabolic profile in menopausal women suggests that, ageing has an effect on the increase of obesity and blood pressure, just as obesity increases blood pressure and changes the metabolic profile.